Divine Trust and Climate Diplomacy: Khilafah Stewardship in Muslim-Majority States’ participation in the 2024 IPEF Clean Economy Agreement - Ilham Dary Athallah; Hayara Khairia; Tsabita Husna; Nadine Rizqi Auliya; Fatahillah Rasyidin (i-Tourism: Jurnal Pariwisata Syariah, 2026)
Abstract This article examines how the Islamic principle of Khilafah – the notion of divinely ordained Earth stewardship – shapes the participation of Muslim-majority partners (Indonesia, Malaysia, Brunei) in the Indo-Pacific Economic Framework for Prosperity (IPEF) Clean Economy Agreement signed in June 2024 Alongside Khilafah, the principle of Istishlah (public interest, Maslahah Mursalah) is operationalized as a co-analytical lens, revealing how state actors apply juristic reasoning about collective welfare to justify international treaty commitments. Drawing on Islamic International Relations theory and extensive analysis of policy documents, ministerial statements, and investment forum data, the study bridges Islamic ethical concepts with empirical climate diplomacy. We operationalize Khilafah as a normative independent variable shaping state behavior through three normative pathways: leaders’ sense of amanah (sacred trust), aversion to fasād (earthly corruption), and pursuit of maṣlaḥah (public welfare). A qualitative, comparative case study methodology is employed to trace how these values manifest in rhetoric and policy choices, contrasted against secular counterparts (e.g. the United States, Australia). The results show that Indonesian, Malaysian, and Bruneian officials frame climate commitments as a moral duty to protect God’s creation and future generations, legitimizing ambitious climate actions beyond material incentives. The discussion highlights how an Islamic stewardship lens reveals motivations and legitimating strategies overlooked by conventional IR theories. The study concludes that Khilafah principles can significantly inform international environmental cooperation, expanding both IR theory and policy praxis.